Revolutionizing Healthcare: Harnessing AI for Antibiotic Stewardship and Precision Medicine - George Edison (BULLET : Jurnal Multidisiplin Ilmu, 2024)
The applications of artificial intelligence (AI) in drug development to combat antibiotic resistance, precision medicine, and antimicrobial stewardship are the main topics of this review, which examines the relationship between AI and antibiotic management and healthcare. The review emphasizes the revolutionary potential of AI in improving patient outcomes, optimizing antibiotic therapy, and tackling the worldwide problem of antibiotic resistance through a thorough analysis of recent research, case studies, and future prospects. The creation of AI-powered prediction models for antibiotic resistance, the incorporation of AI into clinical decision support systems, and the progression of gnomically-driven precision medicine techniques are some of the major themes. In addition, the paper addresses the difficulties and moral questions pertaining to the application of AI in clinical practice, such as concerns about algorithmic bias, data privacy, regulatory compliance, and provider acceptability. Researchers, physicians, legislators, and industry stakeholders can use artificial intelligence (AI) to transform antibiotic management and influence the course of infectious diseases in the future by placing a high priority on openness, cooperation, and interdisciplinary interaction.